Role of YAP1 Signaling in Biliary Development, Repair, and Disease - Molina, Laura; Nejak-Bowen, Kari; Monga, Satdarshan P. (Seminars in Liver Disease, 2022)
Yes-associated protein 1 (YAP1) is a transcriptional coactivator that activates transcriptional enhanced associate domain transcription factors upon inactivation of the Hippo signaling pathway, to regulate biological processes like proliferation, survival, and differentiation. YAP1 is most prominently expressed in biliary epithelial cells (BECs) in normal adult livers and during development. In the current review, we will discuss the multiple roles of YAP1 in the development and morphogenesis of bile ducts inside and outside the liver, as well as in orchestrating the cholangiocyte repair response to biliary injury. We will review how biliary repair can occur through the process of hepatocyte-to-BEC transdifferentiation and how YAP1 is pertinent to this process. We will also discuss the liver's capacity for metabolic reprogramming as an adaptive mechanism in extreme cholestasis, such as when intrahepatic bile ducts are absent due to YAP1 loss from hepatic progenitors. Finally, we will discuss the roles of YAP1 in the context of pediatric pathologies afflicting bile ducts, such as Alagille syndrome and biliary atresia. In conclusion, we will comprehensively discuss the spatiotemporal roles of YAP1 in biliary development and repair after biliary injury while describing key interactions with other well-known developmental pathways.
Keywords: Hippo signaling; bile duct development; cholestasis; transdifferentiation; ductular reaction